One dimensional seismic velocity structure beneath Western Nepal - Rajaure, S. (Journal of Nepal Geological Society, 2002)
An attempt has been made to study the velocity structure of western Nepal. Arrival time data of local earthquakes occurring in that region were used to derive the model. A three layered velocity model both for the P- as well as S-wave velocity has been estimated. The compressional wave velocities in the first, second and the third layers have been estimated to be 5.53 km/sec. 6.29 km/sec and 8.13 km/sec respectively. Similarly the corresponding S-wave velocities are 3.18, 3.62, 4.66 km/sec respectively. The model for the Western Nepal and that for the Centre-East Nepal are almost same. The crust and the mantle beneath west and center-east are homogeneous.